Holocene activity and seismic surface rupture zone of the Abuduo fault eastern Tibetan Plateau - Liao, Cheng; Liang, Mingjian; Chen, Han; Mao, Zebin; Wu, Weiwei; Gong, Yue; Zuo, Hong; Liu, Shuhuai; Li, Tian; Li, Zhongyang (Frontiers in Earth Science, 2024)
The Garzê -Yushu fault is a large active NW-trending strike-slip fault on the Tibetan Plateau, along which strong earthquakes have frequently occurred historically. Together with the Xianshuihe fault, the Garzê -Yushu fault constitutes the northern boundary of the Sichuan-Yunnan block, and it is also the boundary between the Bayan Har and Qiangtang blocks. The Abuduo fault is a near E-Wtrending fault on the southern side of the Garzê -Yushu fault. Through remote sensing image interpretation and field seismic geological investigations, this study found a series of left-lateral displacement landforms and well-preserved seismic surface rupture zones along the Abuduo fault, extending over a distance of approximately 65 km from Abuduo through Yushu and Qinghai to Selikou Village. According to the geological and geomorphological evidence, the Abuduo fault is considered a left-lateral strike-slip fault with Holocene activity, which has tectonic conditions suitable for breeding and generating strong earthquakes. Additionally, the eastward extension of the Abuduo fault is likely to intersect the Garzê -Yushu fault and thereby decompose its horizontal sliding deformation.